EMPOWERMENT OF COMMUNITY HEALTH CADRES THROUGH HEALTH POST MANAGEMENT TRAINING AND HOSPITAL ASSISTANCE TO IMPROVE BASIC HEALTH SERVICES IN MALANG REGENCY - Marlena Ayu Windasari; Vip Paramarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study explores the integrated role of community health cadre empowerment, health post management, and hospital assistance in enhancing the quality and sustainability of primary healthcare services in Malang Regency. The research highlights how the empowerment of community health cadres (CHCs) serves as the foundation for effective grassroots health delivery by improving competence, motivation, and leadership in health promotion and disease prevention. Efficient health post management is identified as a critical mechanism for optimizing service organization, resource utilization, and community participation, ensuring accessibility and continuity of care. Furthermore, hospital assistance acts as a catalyst for quality improvement by providing mentorship, technical supervision, and systematic evaluation that bridge the gap between institutional and community-based healthcare. Using a literature-based analytical approach, the study synthesizes findings from recent research and policy reports to assess the interrelationship between these three components. Results indicate that integrating empowerment, management, and institutional support significantly enhances service performance, strengthens referral systems, and increases community trust in health facilities. The analysis underscores that sustained collaboration among hospitals, community health centers, and local cadres is vital for building an inclusive and resilient healthcare system.